2021
DOI: 10.17263/jlls.903481
|View full text |Cite
|
Sign up to set email alerts
|

Language choices of language teachers and learners: Meta-synthesis of qualitative research

Abstract: This study aims at drawing a conclusion about the use of the first language (L1) in language classes on which there is still no consensus among researchers. In line with this aim, the qualitative studies involving participants' views or practices obtained through interviews or observations were analyzed and then synthesized. Firstly, two basic themes were obtained as "Avoidance of L1 in language classes" and "Use of L1 in language classes". Based on the findings of those studies, the factors such as educationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…The role of learners' L1 has been historically controversial in instructed language learning settings (Macaro et al, 2020), but recently, a significant amount of research has been devoted to analysing the function of L1 in learning an additional language (Bruen & Kelly, 2017;Grant & Nguyen, 2017;Macaro et al, 2020;Molway et al, 2022;Shin et al, 2020;Yıldız, 2021) and suggests that the language learning process can be enhanced by the use of students' L1. Grant and Nguyen (2017) revealed that L1 was used in Vietnamese EFL classrooms for pedagogical purposes and affective purposes.…”
Section: The Affordances Of L1 Use In the Foreign Language Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of learners' L1 has been historically controversial in instructed language learning settings (Macaro et al, 2020), but recently, a significant amount of research has been devoted to analysing the function of L1 in learning an additional language (Bruen & Kelly, 2017;Grant & Nguyen, 2017;Macaro et al, 2020;Molway et al, 2022;Shin et al, 2020;Yıldız, 2021) and suggests that the language learning process can be enhanced by the use of students' L1. Grant and Nguyen (2017) revealed that L1 was used in Vietnamese EFL classrooms for pedagogical purposes and affective purposes.…”
Section: The Affordances Of L1 Use In the Foreign Language Contextmentioning
confidence: 99%
“…teachers' target language proficiency) and contextual differences (e.g. curriculum, policy and institution type) (Shin et al, 2020;Yan et al, 2016;Yıldız, 2021). Hu and Lei (2014) found limited English proficiency was the main reason for Chinese EFL learners to resort to Chinese when tackling difficult vocabulary.…”
Section: Issues Affecting the L1 And Target Language Use In Fl Classesmentioning
confidence: 99%
See 1 more Smart Citation